A quantitative analysis of the relationship between the 12 components of the Index of Economic Freedom (IEF) and the Human Development Index (HDI) scores within the 16 Southern African Development Community (SADC) nations - Peel, Brendon Robert (Rhodes University, Faculty of Commerce, Rhodes Business School)
Nations in Sub-Saharan Africa tend to experience some of the worst levels of human development and economic freedom in the world. Previous research has shown that there is a positive and significant correlation between these two macroeconomic facets. Further research has shown that if nations' policy-makers can manage their resources and capabilities appropriately, then this could improve their economic freedom and human development levels. This study aims to analyse the relationship between the scores of the 12 different components of the Index of Economic Freedom (IEF) and the overall Human Development Index (HDI) scores of Sub-Saharan African nations. The specific selection of nations utilised in the study are the 16 countries that make up the Southern African Development Community (SADC). Based on a review of the literature on human development, economic freedom, and the Resource Based Theory (RBT) on a macro-level, a correlational study was conducted to determine the relationship between the relevant variables. The information was collected from the Heritage Foundation and the United Nations Development Program (UNDP), respectively. The data and scores collected and used in the study are from the years 2015 to 2019. The correlational results demonstrated that nine of the 12 components of the IEF has a positive and significant correlation with HDI within the selected African nations. The strongest correlation being between 'Property Rights' and HDI. Therefore, it is likely that if the property rights within a nation are upheld, said nation would have higher levels of human development. The three components that proved to have an insignificant result with HDI were; 'Tax Burden', 'Government Spending', and 'Fiscal Health'. The results indicate that all components that fall under the category of 'Government Size' share no significant correlational relationship with human development. It is recommended that governments and policy-makers take this into consideration when managing their resources and capabilities to improve the nation's human development. Further research is required to identify the specifics on how this management and allocation of resources can be utilised effectively to improve the human development and economic freedom in Sub-Saharan Africa.
Keywords: Southern African Development Community; Quantitative research; Economic development -- Developing countries; Economic development -- Africa, Sub-Saharan; Economic development projects -- Africa, Sub-Saharan; Heritage Foundation (South Africa); United Nations Development Programme; Index of Economic Freedom (IEF); Human Development Index (HDI); Resource Based Theory (RBT)